The effect of loading time on marginal bone change of implants immediately placed after extraction: a retrospective study - Sung-Jae Lee; Euy-Hyun Kim; Dong-Keon Lee; In-Seok Song; Sang-Ho Jun (SpringerOpen, 2022)
Abstract Background The purpose of this study is to compare and analyze the treatment outcomes between two groups which are both immediately placed implant cases, one is immediate loading, and the other is conventional loading group. Methods Medical records of the patients who underwent implant treatment which were immediately placed after tooth extraction were analyzed. Demographic data were collected and by using periapical or panoramic radiographic image, marginal bone level and distant crestal bone level were measured. Marginal bone change over time was analyzed and compared between immediate loading group and conventional loading group. Results A total of 71 patients, 112 immediately placed implants after tooth extraction were initially involved. Measuring was done with implants which had not failed (81). 10 implants were had failed and removed. The others were excluded because of follow-up loss, absence of radiographic image, etc. Demographic data were collected, and measured values were averaged at each follow-up and showed in linear graphs. Conclusions In case of immediate implantation of dental implant after extraction, loading time could affect marginal bone level or biological width of the implant. Immediate loading group showed 0.92 mm (mean value) more bone loss compared to conventional loading group at bone-implant contact points 24 months after implantation. At distant crestal points, there was no noticeable difference in bone change pattern between two groups.